2022
DOI: 10.1111/pops.12871
|View full text |Cite
|
Sign up to set email alerts
|

Distrustful Complacency and the COVID‐19 Vaccine: How Concern and Political Trust Interact to Affect Vaccine Hesitancy

Abstract: We test the hypothesis that COVID-19 vaccine hesitancy is attributable to 'distrustful complacency'an interactive and not just additive combination of concern and distrust.Across two studies, 9695 respondents across 13 different parts of Britain reported their level of concern about COVID-19, trust in the UK government, and intention to accept or refuse the vaccine. Multilevel regression analysis, controlling for geographic area and relevant demographics, confirmed the predicted interactive effect of concern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 111 publications
3
5
0
Order By: Relevance
“…Vaccine mandate and the further circulation of conflicting information about the vaccines may also associate with ambivalization as one‐fifth (20.2%) of the believers in T2 transited to fence‐sitters in T3 with lowered confidence and heightened complacency. This echoes the previous findings that, to at least some individuals, vaccine mandates could bring psychological reactance and decreased confidence (Betsch et al, 2015; Mignot et al, 2021) and heightened complacency (Lalot et al, 2022). Some individuals might become more complacent and acquire a false sense of security when they are vaccinated, thinking that they are well protected by the vaccines and no longer need to take precautions (Canning et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Vaccine mandate and the further circulation of conflicting information about the vaccines may also associate with ambivalization as one‐fifth (20.2%) of the believers in T2 transited to fence‐sitters in T3 with lowered confidence and heightened complacency. This echoes the previous findings that, to at least some individuals, vaccine mandates could bring psychological reactance and decreased confidence (Betsch et al, 2015; Mignot et al, 2021) and heightened complacency (Lalot et al, 2022). Some individuals might become more complacent and acquire a false sense of security when they are vaccinated, thinking that they are well protected by the vaccines and no longer need to take precautions (Canning et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…The findings add substantially to an emerging body of literature pointing to positive effects of both concern and political trust during the pandemic (Lalot, Abrams, et al., 2022; Lalot, Heering, et al., 2022; Seyd & Bu, 2022; Troiano & Nardi, 2021; Vasilopoulos et al., 2023). Crucially, they consistently reveal the importance of considering the interactive rather than simply separate, additive, role of these factors.…”
Section: Discussionsupporting
confidence: 70%
“…(2022) proposed the distrustful complacency hypothesis that people who are both complacent (about the consequences of the pandemic) and distrustful (of the government) would be least compliant with COVID‐19 regulations. Data from small opportunity samples of respondents in France and Italy during lockdown in spring 2020 supported the hypothesis (see also Lalot, Abrams, et al., 2022; Seyd & Bu, 2022; Vasilopoulos et al., 2023).…”
Section: Introductionmentioning
confidence: 83%
“…These group-based appraisals lead to experiencing group-based emotion, such as trust and social satisfaction. A lot of research has found a positive relationship between trust and compliance behaviors (Burton et al, 2023; Ehrke et al, 2023; Lalot et al, 2023; Miao et al, 2023; Ridenhour et al, 2022; Rudert et al, 2021; Scandurra et al, 2023; Shi et al, 2021).…”
Section: A Social Perspective: the Social Identity Theory And Othersmentioning
confidence: 99%